PREPARATION OF FUTURE SPECIALISTS IN THE FIELD OF LIFE SAFETY AND PHYSICAL CULTURE FOR PROFESSIONAL ACTIVITIES IN THE CONDITIONS OF SOCIETY DIGITALIZATION - Artemov, A.S.; Artemova, Yu.V.; Karaseva, E.N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the readiness of future life safety teachers and specialists in the field of physical education to carry out their professional activities using digital educational technologies. Methods and structure of the study. Experimental testing was carried out at the FSBEI HE “Bunin Yelets State University”. The sample consisted of 100 subjects (control and experimental groups). The reliability of the obtained data was checked using the Mann-Whitney U-test. Results and conclusions. In the educational process with the students of the experimental group, the method of practice-oriented learning was used with the use of modern information, interactive technologies and digital tools. They have been integrated into the process of vocational training and continuing education. The control group of subjects followed the traditional training route. On the basis of a comparative analysis of empirical data and statistical analysis, a positive trend was established in the development of the information and communication criterion indicator of readiness that we identified among the students of the experimental group. The difference between the studied parameters in the subjects of the experimental and control groups was determined at a significance level of p≤0.05.